Chronic exercise increases macrophage-mediated tumor cytolysis in young and old mice - Lu, Q; Ceddia, M A; Price, E A; Ye, S-M; Woods, J A (American journal of physiology. Regulatory, integrative and comparative physiology, 1999)
In this study, we determined the effects of age and chronic treadmill running (16 wk; 5 days/wk; 45 min/day; 18-22 m/min) on resident peritoneal macrophage responsiveness to interferon-γ (IFN-γ) and lipopolysaccharide (LPS) in young (6 mo) and aged (22 mo) male BALB/cByJ mice by measuring cytolytic ability and production of reactive nitrogen products. Macrophages (>90% Mac-3 ) were incubated with various concentrations of IFN-γ and LPS for 24 h. After washing, P815 tumor cells were utilized as targets in a 16-h Cr release assay. We found that aging resulted in a significant reduction in the ability of macrophages to respond to the highest doses of IFN-γ and LPS and kill P815 cells (46 ± 4 vs. 34 ± 2% in young and old mice, respectively). Exercise training significantly increased macrophage cytolysis in both age groups (66 + 7 vs. 44 + 2% in young and old mice, respectively); this effect was larger in the young mice. Macrophages from young exercised mice also produced significantly (50-60%) more[Formula: see text]; there was a tendency for higher[Formula: see text] in old exercisers. The inducible nitric oxide synthase (iNOS) inhibitor N -monomethyl-l-arginine (l-NMMA) significantly reduced macrophage cytolysis and [Formula: see text]production and completely abrogated exercise-induced increases in these measures. RT-PCR analysis revealed significantly higher iNOS mRNA levels in macrophages obtained from the exercise-trained mice and significantly lower iNOS mRNA in old compared with young mice. We conclude that aging reduces and exercise training increases the capacity of resident peritoneal macrophages to respond to IFN-γ and LPS with increased tumor cytolysis. Enhanced iNOS gene expression and[Formula: see text] production are likely the contributing mechanisms of the exercise-induced enhancement of cytolysis in young mice. Whilel-NMMA did block the exercise-induced increase in cytolysis, exercise did not increase[Formula: see text] or iNOS gene expression in the old mice, indicating perhaps the contribution of other cytolytic mechanisms in old mice.